Monet - Rachman, Carla (London Phaidon Press Limited, 2004)
In this clear and engaging account of Monet's life and art, Carla Rachman analyses the development of the artist's work in light of both a changing art market and the social and political context of his time. She argues that Monet's choice of subject matter - whether it was the Gare Saint-Lazare in Paris, Rouen Cathedral or water-lilies at Givenry - was not only a result of his personal vision but also a response to the rapid industrial development of late nineteenth-century France and to the ravages of the Franco-Prussian War and World War I. The result of this book that reveals a complicated artist who was both influenced by events around him and had a formative influence on the history of modern art --Back cover.
Reprint of the 1997 edition.
AL-2430 donated by Prof. Grace Liza Concepcion
Keywords: Monet, Claude, -- 1840-1926.